The Effects of Momordica balsamina Methanolic Extract on Kidney Function in STZ-Induced Diabetic Rats: Effects on Selected Metabolic Markers - Anelisiwe Siboto (Journal of Diabetes Research, 2018)
Background. Studies suggest that Momordica balsamina (intshungu) possesses hypoglycaemic effects. The effects of Momordica balsamina on diabetic complications such as DN, however, have not been established. Accordingly, this study seeks to investigate the effects of M. balsamina on kidney function in STZ-induced diabetic rats. Methods. Methanolic extracts (ME) of M. balsamina’s leaves were used in this study. Short-term effects of M. balsamina methanolic extract on kidney function and MAP were studied in STZ-induced diabetic rats treated twice daily with M. balsamina methanolic extract (250 mg/kg), insulin (175 μg/kg, s.c.), and metformin (500 mg/kg) for 5 weeks. Results. M. balsamina methanolic extract significantly increased Na+ excretion outputs in STZ-induced diabetic rats by comparison to STZ-diabetic control rats. M. balsamina methanolic extract significantly increased GFR in STZ-diabetic rats with a concomitant decrease in creatinine concentration and also reduced kidney-to-body ratio, albumin excretion rate (AER), and albumin creatinine ratio (ACR). M. balsamina methanolic extract significantly reduced MAP in STZ-diabetic animals by comparison with STZ-diabetic control animals. These results suggest that M. balsamina methanolic extract not only lowers blood glucose but also has beneficial effects on kidney function and blood pressure. Conclusion. These findings suggest that M. balsamina may have beneficial effects on some processes that are associated with renal derangement in STZ-induced diabetic rats.